Enhanced fluorescence efficiency and photocatalytic activity of ZnS quantum dots through Ga doping. Issue 2 (1st February 2019) - Poornaprakash, B.; Chalapathi, U.; Vattikuti, S.V. Prabhakar; Sekhar, M. Chandra; Reddy, B. Purusottam; Poojitha, P.T.; Reddy, M. Siva Pratap; Suh, Youngsuk; Park, Si-Hyun
Abstract: Zinc Sulfide (ZnS) quantum dots (QDs) with enhanced fluorescence efficiency and photocatalytic activity have been attained through Ga doping for the first time. Ga-doped ZnS QDs were synthesized via a solvothermal method using Polyethylene glycol (PEG) as a stabilizer. Transmission electron microscopy studies disclosed that the obtained QDs were slightly polydispersed with an average size of 5.5–3.8 nm. The results of X-ray diffraction and Raman and X-ray photoelectron spectroscopy stipulated that the Ga ions were successfully incorporated into the ZnS crystal lattice without amending their internal structure. A blue shift was noticed in the ZnS QDs when doped with Ga. The photoluminescence spectra of all the QDs displayed the same blue emission and enhanced fluorescence efficiency with increase in Ga doping content. The photocatalytic degradation of the phenol red dye under UV-light illumination was enhanced with increasing Ga doping concentration. Thus, the Ga-doped ZnS QDs are potential and favorable candidates for both photoluminescent and photocatalytic device applications.